The complete chloroplast genome sequence of Panax vietnamensis Ha et Grushv (Araliaceae). (2nd January 2017) - Nguyen, Binh; Kim, Kyunghee; Kim, Young-Chang; Lee, Sang-Choon; Shin, Ji Eon; Lee, Junki; Kim, Nam-Hoon; Jang, Woojong; Choi, Hong-Il; Yang, Tae-Jin
Abstract: The complete chloroplast genome sequence of Panax vietnamensis, a medicinal herb belonging to Araliaceae family, was generated by de novo assembly using whole genome next-generation sequences. The chloroplast genome was a circular form of 155 992 bp long and showed typical chloroplast genome structure consisting of a large single-copy region of 86 177 bp, a small single copy region of 17 935 bp and a pair of inverted repeats of 25 940 bp. The chloroplast genome had 79 protein-coding genes, 29 tRNA genes and 4 rRNA genes. The phylogenetic analysis with the reported chloroplast genomes revealed that four Panax species were grouped in the same clade and P. vietnamensis is more closely related to P. notoginseng than P. ginseng and P. quinquefolius .